Electrostatic Particle Ionization for Reduction in Livestock and Potash Dust - Myra Martel; Matthew Taylor; Shelley Kirychuk; Kwangseok Choi; Huiqing Guo; Lifeng Zhang (Atmosphere)
Airborne dust is an important contaminant affecting the health and the environment, and a crucial concern in many workplaces such as animal facilities and potash mines. One of the techniques used for dust control is electrostatic particle ionization (EPI). This technology has been proven effective in reducing airborne dust; however, it has downsides, such as the generation of ozone and corrosion of electrodes. Thus, this study tested a corrosion-resistant carbon-fiber discharge electrode and compared it with electrodes commonly used in EPI systems, that is, stainless-steel and tungsten electrodes, in terms of collection efficiency for potash dust and wheat flour (representative of livestock dust), ozone production, and power consumption. The carbon-fiber electrode performed comparably to stainless-steel electrodes, particularly for potash dust, and performed better than the tungsten electrode in terms of dust collection efficiency. Moreover, it had the lowest energy consumption and generated the least amount of ozone. However, because of the limitations of this study (e.g., fewer samples, low air velocity, controlled conditions, and the use of wheat flour instead of livestock dust), tests under real barn or mining conditions are necessary to confirm the results.